The Role of Religious Education on Islamic Legal Awareness in Relation to Marriage in Kuantan Hilir: Case Study of Unrecorded MarriageÂ Practices - Desminar Desminar; Firdaus Firdaus; Syaflin Halim; Wahyuni Suci (SYAMIL: Journal of Islamic Education, 2024)
ChatGPT This research aims to implement Islamic Religious Education (PAI) to raise awareness of Islamic law regarding unregistered marriages in the Kuantan Hilir District. Employing a qualitative method with a case study approach, primary data was gathered through in-depth interviews with 3 sources and direct observation of 12 perpetrators of serial marriages. Secondary data was collected from various related literature sources. The findings revealed 12 couples in the area engaging in unregistered marriages, predominantly due to pregnancy out of wedlock, with two cases involving arranged marriages. Understanding Islamic law underscores the significance of registering marriages at the Office of Religious Affairs (KUA) to safeguard the legal rights of partners and children, particularly in instances of pregnancy out of wedlock. Knowledge of Islamic marriage procedures underscores the imperative of complete registration at the KUA, especially in cases of pregnancy out of wedlock. Awareness of the legal consequences emphasizes the curtailment of rights for children and wives from unregistered marriages, particularly in situations of out-of-wedlock pregnancy. Attitudes towards Islamic legal education stress its role in diminishing the incidence of unregistered marriages and underscore the importance of marriage registration, particularly in cases of out-of-wedlock pregnancy. The experience of addressing unregistered marriage cases underscores the significant legal issues faced by such couples, particularly concerning children born out of wedlock without registration. Overall, this research underscores the criticality of marriage registration and Islamic legal education in safeguarding the legal rights of spouses and children.